WS: Looking From a Distance: An approach to text analysis with R - Luciano Moreira,; Felipe Jacob Ferreira,; Joana Pinela,; Joel Ramos Faustino,; Raquel Correia de Souza,; Lile Kobaliani,; Thaís Barbedo Vigas,; Lizi Kolbaia, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
In this workshop, we explored a research example on the field of utopian studies and, within it, feminist criticism to illustrate text analysis with R language using metadata from the Lyman Tower Sargent Bibliography. Participants were introduced to the research topic, the R Studio environment, and guided through the iterative process of text analysis (word frequency and network analysis) with the Quanteda library. We aimed to show that visualizations are, more than results, part of a process that triggers new, more complex research questions.